Kajian Komparatif: Gotong Royong dalam Pepatah Mamasa dan Tana Ai untuk Kohesi Sosial - Kristian Kristian; Pangkrasio Raul Dharma Putra; Reski Kresensia (Fakultas Teologi, Universitas Sanata Dharma, 2026)
Gotong royong (mutual cooperation), which serves as a vital pillar of social cohesion in Indonesian society, is deeply embedded in community life and articulated through various local proverbs. Modernization and the influence of individualistic lifestyles are causing the values of gotong royong to fade and become increasingly difficult to practice in daily life. This study aims to examine two proverbs from different ethnic groups: